EFL TEACHERS' PERCEPTIONS OF AI'S IMPACT ON ACADEMIC INTEGRITY AND PEDAGOGY IN BANGLADESHI UNIVERSITIES - Islam, Mirajul; Hasan, Md. Mahadhi; Mahmud, Rashed (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
The objectives of the research are to identify Bangladeshi EFL teachers’ perceptions regarding the role of AI in language teaching in the way it affects academic integrity, the pedagogical issues, and how these can affect the efficacy of the existing institutional policies in English teaching profession. This study used a descriptive quantitative research design, which is based on an online questionnaire survey with 115 EFL teachers teaching in 22 private universities in Bangladesh. The results found that 69.6% of teachers were concerned about the ethical implications of AI, most prominently 69.6% about the alignment with academic dishonesty. In addition, 65.2% of the teachers revealed challenges in merging AI into class pedagogy, with the foremost reason being a lack of institutional support and training provision to integrate the lessons into class lessons. Indicatively, 74.8% of respondents stated that current institutional policies do not enable dealing with the challenges posed by AI in education. The study recommends the immediate requirements for extensive AI-related training programs, institutional regulations, and instruments to attain academic integrity in EFL classrooms. This research builds on and adds to the growing literature on AI in education while capturing the Bangladeshi EFL context. Future research can be conducted on the threats of AI-integration in EFL teaching and learning.